Oedipus and the Crisis of Humanism. - Ionescu, Mădălina (Caietele Echinox, 2025)
Sophocles' tragedy foregrounds Oedipus's humanistic qualities. Oedipus embodies a human-centered world, showcasing remarkable wisdom in solving the Sphinx's riddle and unhesitating loyalty to Thebes. Posthumanism's current state questions the Western humanist tradition, demanding a renewed look at the human values presented in the (post)modern reinterpretations of the myth. By choosing not to take any action, Vlad Zografi's Oedipus believes he can avoid tragedy in this version of the play. Therefore, the Theban hero attempts to escape his destiny through inaction, a choice that compels a reassessment of what truth and free will represent within the contemporary theoretical framework. In this article, I assess the Oedipal figure's significance in representing the modern human subject's crisis within a context of simulacra, post-truth and post-temporality.